Additive migration from plastics into food - Crompton, T. R. (Thomas Roy) (Pergamon Press, 1979)
Additive Migration from Plastics Into Food examines the intrusion of foreign chemicals into food via additives present in plastics packaging and the toxic hazards they pose to consumers. This book shows how direct contact between the packed commodity and the plastic is likely to result in the transfer of polymer additives, adventitious impurities such as monomers, catalyst remnants, and residual polymerization solvents, and low-molecular-weight polymer fractions from the plastic into the packaged material. This book is comprised of nine chapters and begins with a discussion on the various typ.